Spatial and Temporal Trends in HIV/AIDS Burden Among Worldwide Regions From 1990 to 2019: A Secondary Analysis of the Global Burden of Disease Study 2019 - He, Huan; Ou, Zejin; Yu, Danfeng; Li, Yongzhi; Liang, Yuanhao; He, Wenqiao; Gao, Yuhan; Wu, Fei; Chen, Qing (Frontiers in Medicine, 2022)
Purpose HIV/AIDS is a critical public health concern worldwide. This article investigated the speed of temporal changes in HIV/AIDS burden from 1990 to 2019. Methods Data was extracted from the Global Burden of Disease(GBD) Study of 2019. The estimated annual percentage change (EAPC) and the age-standardised rate (ASR) were used to quantify the temporal trends at global, regional, and national levels. Results During the period 1990–2004, the overall incidence of HIV/AIDS was relatively stable. However, trends in prevalence, death, and disability-adjusted life years (DALYs) showed rapid increasing trends, with respective EAPCs of 7.47 (95% confidence interval [CI] 5.84, 9.12), 10.85 (95% CI 8.90, 12.84), and 10.40 (95% CI 8.47, 12.36), respectively, especially in low-resource regions. During the period 2005-2019, the global trends in incidence, death and DALYs of HIV/AIDS decreased, with the EAPCs of −2.68 (95% CI −2.82, −2.53), −6.73 (95% CI −6.98, −6.47) and −6.75 (95% CI −6.95, −6.54), respectively. However, the disease prevalence showed slight increasing trend (EAPC = 0.71, 95% CI 0.54, 0.87). Conclusions Decreasing trends in HIV/AIDS incidence, death, and DALYs have been observed worldwide over the past 15 years, especially in death and DALYs rates. However, the global population living with HIV/AIDS is increasing with a prevalence showing an increasing trend, suggesting that prevention and control of HIV/AIDS still need to be strengthened to counteract these concerning trends